id_ID Pembingkaian Ulang Paratekstual dalam Penerjemahan: Narasi Sosial menurut Baker - Prihantono, Kahar Dwi (Jurnal Penerjemahan, 2025)
Translation can be viewed as a mode of (re)narration as it actively contributes to constructing the worldrather than simply functioning as a mechanism for transferring meaning from one language to another. This study delves into the role of paratext in reframing or (re)constructing various narratives concerning a translated work, Stuart Robson’s The Wedhatama, and highlights how the translator has strategically taken advantage of those paratextual elements to reinterpret the Javanese literary work and to promote his ideological viewpoints. By applying Baker’s social narrative approach, this study identifies that Robson presented personal reflections in his translation and shed light on the personal narrative of the ambiguous authorship of Serat Wedhatama[1]; public narratives presenting some clues might have provided its author with inspiration or impulse to write,under the glory of the Mangkunegaran, stories related to the governments, which flourished under the capable leadership of Mangkunegara IV, and stories about challenging the existing meta-narratives: Panembahan Senapati versus The Prophet, and kejawen versus pure Islam. Finally, Robson presented conceptual narratives, stating that the original work of Serat Wedhatama conveys a profound sense of cultural identity of the noble class. The paratextual elements present in the translation can assist target readers in understanding the translation and enhance the wider cultural narratives, thus playing an active role in the meaning-making process. Serat Wedhatama is believed as a prominent Javanese poetic work known for its ethical and philosophical teachings, especially concerning the concept of divinity and the importance of character education